1991
DOI: 10.1079/bjn19910077
|View full text |Cite
|
Sign up to set email alerts
|

Maternal undernutrition during mid-pregnancy in sheep. Placental size and its relationship to calcium transfer during late pregnancy

Abstract: ~ ~~-The aim of the present experiment was to determine the relationship between placental and fetal weight after placental growth had been retarded by maternal undernutrition. Placental weight and fetal weight were measured in single-lamb-bearing ewes which were well-fed throughout pregnancy, or severely undernourished between the 30th and 96th day of pregnancy. Placental transfer of calcium and wholebody metabolism of both glucose and Ca were measured during late pregnancy. The change in fleeceadjusted live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 32 publications
(30 reference statements)
5
41
0
Order By: Relevance
“…Clearly, detailed examination of maternal body composition following nutrient restriction in early to mid gestation is required to determine if this is accompanied by appreciable loss of maternal fat stores. The observation in the present study that nutrient restriction was associated with a smaller rather than a larger placenta as observed when ewes are under-fed and lose weight (McCrabb et al 1991), suggests that major factors determining placental, and possibly fetal responses to nutrient restriction are both maternal body weight (McCrabb et al 1992;Robinson et al 1994) and body conformation (Clarke et al 1997).…”
Section: Maternal and Fetal Responses To Nutrient Restrictionmentioning
confidence: 77%
See 1 more Smart Citation
“…Clearly, detailed examination of maternal body composition following nutrient restriction in early to mid gestation is required to determine if this is accompanied by appreciable loss of maternal fat stores. The observation in the present study that nutrient restriction was associated with a smaller rather than a larger placenta as observed when ewes are under-fed and lose weight (McCrabb et al 1991), suggests that major factors determining placental, and possibly fetal responses to nutrient restriction are both maternal body weight (McCrabb et al 1992;Robinson et al 1994) and body conformation (Clarke et al 1997).…”
Section: Maternal and Fetal Responses To Nutrient Restrictionmentioning
confidence: 77%
“…The extent to which such changes in blood flow and cell development can act to maintain fetal growth and determine later placental function remains to be determined. These alterations in placental development may have a significant effect on placental mass at term as it has been shown that a loss of body weight or condition score in early-mid gestation, followed by adequate nutrition in late gestation can result in a greater (McCrabb et al 1991) or smaller placental mass (Clarke et al 1997), depending in part on maternal body weight.…”
Section: Nutrient Restriction and Placental Developmentmentioning
confidence: 99%
“…The placentomes reach a maximum weight by approximately day 75 to 80 of gestation (term 150 days) whilst 80% of fetal growth occurs in the final third of gestation (Ehrhardt & Bell 1995, Wallace et al 1999. In early to mid-pregnancy, insults such as inappropriate maternal nutrition and thermal stress can significantly disrupt placental development and subsequent fetal growth (McCrabb et al 1991, 1992, Vatnick et al 1991a, Galan et al 1999. The factors responsible for modifying placental growth are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Nuchal cord encirclements are detected several weeks prior to labour and delivery (Collins et al 1995) and therefore the mechanisms underlying the decreased birth weight are likely to involve a reduction in umbilical blood flow and thus altered nutrient and/or oxygen delivery. The increased placental weight may represent an adaptive overgrowth to sustain nutrient supply, as seen in humans with mild hypoxaemia at high altitude (see Barker 1994) and in some instances of maternal undernutrition in sheep (McCrabb et al 1991).…”
Section: Introductionmentioning
confidence: 99%